Effect of mechanical-strain-induced defect generation on the performance of flexible amorphous In–Ga–Zn–O thin-film transistors. (4th November 2016) - Liao, Po-Yung; Chang, Ting-Chang; Su, Wan-Ching; Chen, Yu-Jia; Chen, Bo-Wei; Hsieh, Tien-Yu; Yang, Chung-Yi; Huang, Yen-Yu; Chang, Hsi-Ming; Chiang, Shin-Chuan
Abstract: In this study, we investigate the effect of mechanical strain on the performance of flexible amorphous In–Ga–Zn–O (a-InGaZnO) thin-film transistors. Drain current–gate voltage ( I D – V G ) and capacitance–voltage ( C – V ) transfer curves are measured to analyze the degradation behavior. The I D – V G characteristic exhibits a clear negative shift under mechanical strain regardless of the tension or compression state. In addition, the C – V characteristic curves show a leftward shift with extra distortion or stretching out under mechanical strain. This indicates that InGaZnO generates additional defects under this mechanical strain, a phenomenon that can be attributed to the generation of mechanical-strain-induced oxygen vacancies on the flexible a-InGaZnO TFTs.